Bilateral cervix apex clamping procedure can be used as a new noninvasive second line therapy for postpartum hemorrhage. (October 2019) - Jiang, Li
Abstract: In this study, we present a noninvasive procedure of bilateral cervix apex clamping (BCAC) procedure to control refractory postpartum hemorrhage (PPH) in vaginal delivery as a new second line therapy for refractory PPH. The procedure clamps the anterior and posterior walls of the cervical apex using toothless ovum forceps to arrest bleedingafter the failure of the first line therapy for PPH. 44 women were performed BCAC to control persistent bleeding in 13, 359 vaginal deliveries from 1 January 2016 to 31 May 2018. In all of the BCAC, it can reduce bleeding significantly. The bleeding speed after BCAC was far less than that before it (2.64 ± 4.99 ml/min vs 20.23 ± 9.40 ml/min P < 0.001). The blood loss after BCAC was less than that before it (146.57 ± 170.83 vs 797.84 ± 200.73 ml P < 0.001). 41 (93.2%) BCACsucceeded and 3(6.8%) failed turned to intrauterine balloon tamponade, 2 succeeded and 1 failed turned to hysterectomy. In the successful group the bleeding speed after the BCAC was 1.38 ± 0.99 ml/min less than that 19.84 ± 6.27 ml/min in the failure group. (p < 0.001). The blood loss in the success group is also less than that in the failure ones after BCAC (107.29 ± 78.36mL vs 683.33 ± 202.07 ml P < 0.001) Even in the failure group, the bleeding speed also reduced after BCAC compared with that before BCAC (19.84 ± 6.27 vs 29.17 ± 7.12 ml/min p = 0.02). But the blood loss had no statistical difference (683.33 ± 202.07 vs 950 ± 132.29 ml p = 0.27) In all of the 13, 359 vaginal deliveries, the incidence of PPH was 1.21% while the severe PPH was only 0.27%. The BCAC may reduce the incidence of severe PPH (0.27%) and also can reduce the necessity of IUBT (3/13, 359 0.22‰), uterine artery embolization (UAE) (0/13, 359) and even the exploratory laparotomy hysterectomy (1/13, 359). Because it is effective, convenient, cheap and noninvasive, so we think it can be used as a new second line noninvasive treatment for PPH.